Average shear rate in airlift bioreactors: searching for the true value - Esperanca, Mateus N. (2019)
The shear rate is an important bioreactor parameter that needs to be evaluated due to its impact on microorganism morphology and viability, and consequently on bioproduct formation. Airlift bioreactors, classified as low-shear devices, are used as an alternative to conventional stirred-tank reactors. Considerable efforts have been made to characterize the shear environments in airlift bioreactors, using the average shear rate as a key parameter. However, there is no agreement among the values obtained in different studies, which can differ even in orders of magnitude. The methodologies used to obtain av in the different studies could be the reason for the lack of agreement among them. In this work, av in a concentric tube airlift bioreactor was evaluated using computational fluid dynamics (CFD), as well as based on universal velocity profiles for liquid flows in smooth pipes and annuli. Good agreement was obtained between the CFD-based average shear rates and the values obtained from universal velocity profiles, indicating that CFD simulation is a valuable tool for av prediction.